DNA-nanostructure-templated assembly of planar and curved lipid-bilayer membranes - Elbahnasawy, Mostafa A.; Nasr, Mahmoud L. (Frontiers in Chemistry, 2023)
Lipid-bilayer nanodiscs and liposomes have been developed to stabilize membrane proteins for their functional and structural studies and biomedical applications. Nanodiscs are detergent-free, water-soluble, size-controlled planar phospholipid-bilayer platforms. Liposomes are curved bilayer spheres with an aqueous core used as drug delivery systems and model membrane platforms for studying cellular activities. A long-standing challenge is the generation of monodispersed lipid-bilayer system with a very wide range of dimensions and curvatures (elongation, bending, and twisting). DNA-Origami templating provides a way to control the shapes, sizes, and arrangements of lipid-bilayer structures via enforcing the assembly of lipid-bilayer within the cavities created by DNA-Origami. Here, we provide a concise overview and discuss in detail how to design planar and curved lipid-bilayer membranes by using DNA-Origami nanostructures as templates. Finally, we will discuss the potential applications of DNA-Origami nanostructures in the structural and functional studies of large membrane proteins and their complexes.